Al-Syawāż al-Naḥwiyyah wa al-Ṣarfiyyah fi Ḥāsyiyah al-Ṣabbān ‘ala Asymūnī (Dirāsah Lugawiyyah Mi’yariyah) - Ali Burhan (ALSINATUNA, 2021)
Occasionally the number of fluent shahids cannot be a barometer in building the Nahwu Sharf rules, because it may be sima’i which cannot be practiced. Likewise, the form of syadz or anomaly that been formulated by nahwu experts is inversely propotional to the number of fluent texts as the main barometer of language rules so that in fact this form can be accepted qiyasi. This background encourage the author to conduct an in-dept study of the relationship of qiyas, sima’i on the side and the fluent texts and anomalous forms in the study of nahwu sharf on the other. The Author used manhaj mi’yari/ standard linguistic methode in this article by taking samples of anomalies pola in the Hasyiyah Sabban Syarh Asymuni’s book. After conducting a critical analysis through a thematic study of the form of anomalies in the nahwu sharf methode in the above book, the writer found that the justification of the nahwu sharf anomalies only focused on shahid/ tekxts whose source in unknown, this is consensus of the Basrah school of thought. The reinforced by fluent texts is not of the same degree. The form of this rule is not an anomaly because it comes from a fluent source that is a reference to the language rules, but it also cannot be made a standard for the formulation of the rules because ther is no general qiyas.